2018
DOI: 10.1016/s1470-2045(18)30364-4
|View full text |Cite
|
Sign up to set email alerts
|

Biological material collection to advance translational research and treatment of children with CNS tumours: position paper from the SIOPE Brain Tumour Group

Abstract: Paediatric CNS tumours are the most common cause of childhood cancer-related morbidity and mortality, and improvements in their diagnosis and treatment are needed. New genetic and epigenetic information about paediatric CNS tumours is transforming the field dramatically. For most paediatric CNS tumour entities, subgroups with distinct biological characteristics have been identified, and these characteristics are increasingly used to facilitate accurate diagnoses and therapeutic recommendations. Future treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 75 publications
1
9
0
Order By: Relevance
“…The vast majority (88%) had completed diagnostic assessment within 23 days of receipt at the NRC; delays were typically due to personnel availability, the requirement for repeat analyses and further CPR. Insufficiency of submitted biomaterials was apparent, and we concur with previous recommendations 21 that a minimum of 1.5 cm 3 of FFPE tissue and 0.5 cm 3 of frozen tumour tissue should be collected where possible. However, in this study we found that the quality of frozen tumour material was a greater risk to successful delivery of molecular diagnostics.…”
Section: Discussionsupporting
confidence: 87%
“…The vast majority (88%) had completed diagnostic assessment within 23 days of receipt at the NRC; delays were typically due to personnel availability, the requirement for repeat analyses and further CPR. Insufficiency of submitted biomaterials was apparent, and we concur with previous recommendations 21 that a minimum of 1.5 cm 3 of FFPE tissue and 0.5 cm 3 of frozen tumour tissue should be collected where possible. However, in this study we found that the quality of frozen tumour material was a greater risk to successful delivery of molecular diagnostics.…”
Section: Discussionsupporting
confidence: 87%
“…The high costs of equipment and the low training options for neuropathologists are well‐known obstacles in LMIC, and might explain the dificulties in the implementation of recommendations to expand histopathological diagnostic studies 19 . However, the importance of molecular brain tumor diagnostics for choosing the best possible therapy is increasing rapidly as its value is more and more recognized 20,21 . If after the Board discussion, a histopathological review was undertaken, usually because of unclear diagnosis or in cases where difficulties in diagnostic apporaches can be expected, the histological diagnosis was refined or changed in almost half of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…Practices developed through SIOP PNET5 MB have introduced standardised real-time centralised molecular diagnostics and pathology review for medulloblastoma patients across Europe, for the first time. These are supported by the introduction of contemporary practices for the routine collection of high-quality samples (i.e., fresh-frozen and FFPE tumour material, blood (all mandatory) and CSF (optional), essential for clinical and research investigations [ 72 ]. A biology and pathology group within the SIOPE embryonal tumours group works to establish, undertake, coordinate and quality control these processes [ 73 ], together with translational biological studies, within SIOPE medulloblastoma clinical trials; the committee has representatives from all partner countries.…”
Section: Biological Investigations: Reference Assessments and Biological Studiesmentioning
confidence: 99%